Compactação em latossolos e argissolo e relação com parâmetros de solos e de plantas - Collares, Gilberto Loguercio (2005)
Soil compaction is closed related to agriculture as well as animal production management. Soil quality improvement has not been always achieved with use of soil conservation practice as no-tillage or use of animal production integrated to agriculture management. Agricultural traffic and soil management effects on soil compaction are not well known, specially associated to wet soils, and in many cases, has induced to compaction states which restrict crop growth and productivity, which in turn, has lead farmers to break the compaction using mechanical tools as plow or chisel. To better understand compaction effects and critical values of soil physical properties on black beans growth and productivity four studies were set up out in the field. Another field study were performed in five typical dairy farms in Rio Grande do Sul plateau which use systems with agriculture integrated with animal production, including forage management and time of grazing. The objective of this study was to study animal trampling effects on soil physical properties, bulk density, porosity and soil resistance. The first experiment cultivated black beansi in a clayey Oxisol with the following treatments: a) immediate compaction caused by traffic of 16.6 Mg front buck loader; b) chiseling and; c)residual compaction from six years no-tillage. The additional compaction affected mass-volume relations, soil moisture and resistance, a well as black beans growth and productivity. The other three experiments were carried out in an Alfisol from central depression of Rio Grande do Sul with objectives to compare effects of immediate and residual compaction and soil chiseled on soil physical properties and black beans growth and productivity. The immediate compaction was obtained by traffic of a 9 Mg buck loader on present soil condition and on soil compacted with 10 Mg one year ago. For studied Alfisol the bulk density which restricted crop growth and productivity had value higher than 1.7 Mg m-3. The state of compaction with bulk density higher than 1.8 Mg m-3 and macroporority lower than 0.1 m3 m-3 reduced black beans height, leaf area index and crop productivity in abou 50%. The negative effects of additional compaction were maintained after twelve months and succession of three crops (soybeans, oats and black beans), reducing the black benas productivity in 61.8 %. Breaking compaction of a Oxisol under six no-tillage or Alfisol under twelve years no-tillage by soil chiseling did not improve soil quality which induce significant black benas productivity. The bulk density expressed the increase of soil compaction caused by animal trampling, reaching values of 1.77 Mg m-3, measured immediately after animal trampling and, was more significant at superficial layers where the effects on macroporosity were greater.